Influence of elevated temperature on compressive strength of rubberized ultra-high performance concrete - Mohamad Amirulnain, Adi (2017)
Ultra-High Performance Concrete (UHPC), is a high-strength, ductile material formulated by combining ordinary Portland cement, silica fume, quartz flour, fine silica sand, water and steel or organic fibers. It is state that the strength of UHPC has more than 100 MPa compressive strength. The successful production of UHPC depends on its material ingredients and mixture proportioning, which leads to denser and relatively more homogenous particle packing. A series of UHPC mix proportion was designed by replacing the conventional sand with waste rubber chipped (WRC) and Waste Rubber Powder(WRP). The levels of replacement comprise of 5%, 10% and 15% of WRC and WRP from the weight of sand used. In this study, the effects of elevated temperatures at 100°C, 180°C and 260°C on the compressive strength of rubberized-UHPC was studied. The weight loss ratio of the rubberized-UHPC also was taken to compare the percentage of weight loss before and after the heat treatment. The result shows that the inclusion of WRC and WRP in UHPC mix recorded no enhancement in strength as compared to plain UHPC. However, UHPC with 5% WRC and WRP shows a comparable to that plain UHPC. It also found that the compressive strength at 100 °C was higher as compared to other temperatures for 5% mix at 28 days curing and it is comparable to other temperature. For weight loss, the result show the percentage of weight loss was gradually increase with percentage of WRC and WRP for 7, 14 and 28 days . The higher weight loss obtained after the specimen was heated at 260°C for 28 days.